Biopolymeric Nanogel as a Drug Delivery System for Doxorubicin—Improved Drug Stability and Enhanced Antineoplastic Activity in Skin Cancer Cells - Lyubomira Radeva; Maya M. Zaharieva; Ivanka Spassova; Daniela Kovacheva; Ivanka Pencheva-El Tibi; Hristo Najdenski; Krassimira Yoncheva (Pharmaceuticals, 2024)
In this study, doxorubicin was loaded in a chitosan–albumin nanogel with the aim of improving its stability and exploring the potential of the system in the treatment of skin cancer. Infrared spectroscopy and X-ray diffraction confirmed the encapsulation of the drug. Transmission electron microscopy revealed the spherical shape of the nanogel particles. The drug-loaded nanogel was characterized with a small diameter of 29 nm, narrow polydispersity (0.223) and positive zeta potential (+34 mV). The exposure of encapsulated doxorubicin to light (including UV irradiation and daylight) did not provoke any degradation, whereas the nonencapsulated drug was significantly degraded. In vitro studies on keratinocytes (HaCaT) and epidermoid squamous skin carcinoma cells (A-431) disclosed that the encapsulated doxorubicin was more cytotoxic on both cell lines than the pure drug was. More importantly, the cytotoxic concentration of encapsulated doxorubicin in carcinoma cells was approximately two times lower than that in keratinocytes, indicating that it would not affect them. Thus, the loading of doxorubicin into the developed chitosan–albumin nanogel definitely stabilized the drug against photodegradation and increased its antineoplastic effect on the skin cancer cell line.